2018
DOI: 10.1002/ptr.6189
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene lactones‐enriched fraction of Inula helenium L. induces apoptosis through inhibition of signal transducers and activators of transcription 3 signaling pathway in MDA‐MB‐231 breast cancer cells

Abstract: Inula helenium L., commonly known as Elecampane, has been extensively used for many countries in the folk medicine. Its root is a rich source of sesquiterpene lactones, which possess various pharmacological activities. To develop the phytomedicine including sesquiterpene lactones, we prepared hexane fraction from I. helenium (HFIH) and examined the inhibitory effect of HFIH on signal transducers and activators of transcription 3 (STAT3) activation in human breast cancer MDA-MB-231 cells. Additionally, detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Moreover, related to its role in cellular proliferation, multiple studies have demonstrated that STAT3 signaling is associated with cellular apoptosis [ 49 , 50 , 51 ]. The suppression of STAT3 signaling has been reported to promote apoptosis in several human cancer cells including breast cancer cells [ 49 , 50 , 52 ]. Following this observation, we checked whether pentadecanoic acid has the ability to induce apoptosis in MCF-7/SC.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, related to its role in cellular proliferation, multiple studies have demonstrated that STAT3 signaling is associated with cellular apoptosis [ 49 , 50 , 51 ]. The suppression of STAT3 signaling has been reported to promote apoptosis in several human cancer cells including breast cancer cells [ 49 , 50 , 52 ]. Following this observation, we checked whether pentadecanoic acid has the ability to induce apoptosis in MCF-7/SC.…”
Section: Resultsmentioning
confidence: 99%
“…A recent research has reported that downregulation of zinc-finger gene DPF3 (also known as CERD4) promotes proliferation and motility of breast cancer via activating JAK2/STAT3 pathway [32]. It has been reported earlier that STAT3 can upregulate cyclin D-1, c-myc, and bcl-2 to suppress the apoptosis of breast cancer cells, indicating a potential involvement of STAT3 in cell cycle and survival [33]. Moreover, STAT3 activated by IL-6/JAK2 pathway can inhibit Bax/Bcl-2-related caspase-dependent apoptosis [34].…”
Section: The Role Of Stat3 In Breast Cancer Proliferation and Apoptosismentioning
confidence: 98%
“…Similarly, schisandrin A is found to reverse doxorubicin resistance via inhibition of STAT3 phosphorylation in breast cancer [93]. Chun et al have found that the hexane fraction from I. helenium (HFIH) can inhibit STAT3 phosphorylation at tyrosine 705 [33]. Niclosamide, that was reported to be a potent STAT3 inhibitor in TNBC cells, was found to overcome the radioresistance in TNBC cells via inhibition of STAT3 and Bcl-2 activation and induction of reactive oxygen species (ROS) [97].…”
Section: Compounds Inhibiting the Activation Of Stat3 In Breast Cancermentioning
confidence: 99%
“…Among them, the function of STAT3 has been extensively studied as a central mediator of cancer metastasis and a potent target of anticancer drugs [15]. STAT3 upregulates cyclin D1, c-Myc, and Bcl-2 to maintain the survival of tumor cells [16]. STAT3 also advances metastasis by upregulating EMT-associated genes such as twist, snail, slug, vimentin, MMP2, and MMP9.…”
Section: Introductionmentioning
confidence: 99%